RFX Proteins, a Novel Family of DNA Binding Proteins Conserved in the Eukaryotic Kingdom - P. Emery; Bénédicte Durand; Bernard Mach; Walter Reith (1996)
Until recently, the RFX family of DNA binding proteins consisted exclusively of four mammalian members (RFX1-RFX4) characterized by a novel highly conserved DNA binding domain. Strong conservation of this DNA binding domain precluded a precise definition of the motif required for DNA binding. In addition, the biological systems in which these RFX proteins are implicated remained obscure. The recent identification of four new RFX genes has now shed light on the evolutionary conservation of the RFX family, contributed greatly to a detailed characterization of the RFX DNA binding motif, and provided clear evidence for the function of some of the RFX proteins. RFX proteins have been conserved throughout evolution in a wide variety of species, including Saccharomyces cerevisiae, Schizosaccharomyces pombe, Caenorhabditis elegans, mouse and man. The characteristic RFX DNA binding motif has been recruited into otherwise very divergent regulatory factors functioning in a diverse spectrum of unrelated systems, including regulation of the mitotic cell cycle in fission yeast, the control of the immune response in mammals, and infection by human hepatitis B virus.